PENERAPAN MODEL PEMBELAJARAN OEL UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS MATERI ALAT PENCERNAAN MANUSIA PADA SISWA KELAS V SDN KERTOSARI I MADIUN - Naniek Kusumawati; Vivi Rulviana (Jurnal Bidang Pendidikan Dasar, 2020)
AbstractThis research is a classroom action research. The subject of this study was a fifth grade student at SDN Kertosari I Madiun. The results of the research in the first cycle showed the average results of observations of student activities obtained by the percentage of 56.25% with sufficient categories, the percentage of teacher activity 84.37% in the good category. In the second cycle the average percentage of teacher activity was 100% with a very good category, the percentage of 93.75% student activity was very good category. From the completeness of learning outcomes can be compared to the increase, namely from the Pre Cycle, Cycle I and Cycle II amounted to 9.5%, 67.8% and 84.04%. This has met the predetermined indicators of success with a minimum value of 70 learning outcomes and classical completeness already achieve a minimum indicator of success of ≥ 75%. Based on the results of these studies, it can be concluded that the OEL Learning Model can improve the science process skills of human digestive tract material in fifth grade students of SDN Kertosari I Madiun. Abstrak Penelitian ini merupakan penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas V SDN Kertosari I Madiun. Hasil penelitian pada siklus I menunjukkan rata-rata hasil observasi aktivitas siswa diperoleh persentase 56.25% dengan kategori cukup, persentase aktivitas guru 84.37% kategori baik. Pada siklus II diperoleh rata-rata persentase aktivitas guru sebesar 100 % dengan kategori sangat baik, persentase aktivitas siswa 93,75 % kategori sangat baik. Dari ketuntasan hasil belajar dapat dibandingkan peningkatannya yaitu dari Pra Siklus, Siklus I dan Siklus II adalah sebesar 9.5%, 67.8% dan 84.04%.Hal ini telah memenuhi indikator keberhasilan yang telah ditetapkan dengan nilai rata-rata hasil belajar minimal 70 dan ketuntasan klasikal sudah mencapai indikator keberhasilan minimal ≥ 75 %. Berdasarkan hasil penelitian tersebut maka bisa disimpulkan bahwa Model Pembelajaran OEL dapat meningkatkan keterampilan proses sains materi alat pencernaan manusia pada siswa kelas V SDN Kertosari I Madiun.